Marcadores oxidantes e antioxidantes em populações expostas ao mercúrio em diferentes regiões geográficas do estado do Pará, Amazônia brasileira - OLIVEIRA, Claudia Simone Baltazar de (Universidade Federal do Pará, 2017)
This work has objective assess the levels of Hg-T, oxidative stress and antioxidants defenses in populations consumers of fish of different ecosystems from Amazônia. The communities selected for study are: Samaúma, Caratateua, and Barreiras all located in State of Pará. Participated 51 residents from Samaúma, 96 from Caratateua and 52 from Barreiras, of both sexes, between 13 and 55 years. Were collected samples of hair and blood during the visits in the communities for analysis of Hg-T and biochemistry oxidative and antioxidative in 2013. The dosage of GSHtotal, GSSG and GSH was performed in field. For quatification of TEAC and MDA, the samples were frozen and analyzed in the laboratory of oxidative stress of NMT. The analysis of Hg-T were performed in the laboratory of human toxicology and environmental of NMT.The Hg-T in Samaúma was 0.9 μg/g. Caratateua 1.9 μg/g , maximum 20.7 μg/g. Barreiras 4.6 μg/g and maximum 15.7 μg/g of Hg-T. In the dosage of Hg was noted difference statistics very sigficant between the communities. As for frequency of consume of fish, the levels of Hg-T from Caratateua and Barreiras were different statistically when compared to levels of Samaúma in the categories > 2 meals. The relationship between GSSG/GSH was larger in the community of Barreiras, 10. Caratateua and Barreiras presented levels of TEAC similar statistically 0,6 mm/L. In the dosage of MDA, Caratateua presented the larger levels, 3.1 ml/MDA, differing statistically the others comunidades. Only Barreiras community presented weak negative correlation between the levels of Hg-T and GSH. Concluded that The population from Samaúma and Barreiras presented smaller and larger degree of exposure to Hg respectively. However, 11% community of Caratateua presented levels above of recommended by OMS. Barreiras and Caratateua presented larger of degree of cellular oxidation. Thus, there is need for more studies in the community of Caratateua. Besides the application of educational measures in food, as: introduction of antioxidants, the choice of fish species and variability in the diet.